What makes a truly prosperous society? Coexistence & cooperation for the future of Asia & Oceania - Goh, Sin Kok (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This short essay was submitted as part of the application for the 2006 JAL Scholarship Program, organised by Japan Airlines International Co. Ltd. In this short essay, the writer shares his ideas on the necessary elements for achieving a truly prosperous society and how he may contribute towards achieving this goal of a truly prosperous society